Evaluation of a novel Scheimpflug-based non-contact tonometer in healthy subjects and patients with ocular hypertension and glaucoma. Issue 11 (22nd August 2013) - Reznicek, Lukas; Muth, Daniel; Kampik, Anselm; Neubauer, Aljoscha S; Hirneiss, Christoph
Abstract : Background: To evaluate the agreement of intraocular pressure (IOP) and central corneal thickness (CCT) measurements obtained with the non-contact tonometer Corvis Scheimpflug Technology (Corvis ST, OCULUS, Wetzlar, Germany) versus Goldmann applanation tonometry (GAT) and ultrasound-based corneal pachymetry (US-CCT). Methods: Eye healthy participants, patients with ocular hypertension (OHT) and patients with open-angle glaucoma were included in this prospective study. In each participant, GAT, US-CCT and measurements with Corvis ST were obtained (Corvis-IOP and Corvis-CCT). Accuracy and repeatability were tested by correlation and regression analyses, Bland-Altman plots and assessment of intraclass correlation coefficients. Results: A consecutive series of 188 right study eyes of 188 participants (142 eyes with glaucoma, 10 eyes with OHT and 36 control eyes) were included in this prospective study. The mean GAT of all included was 14.5±4.8 mm Hg compared with mean Corvis-IOP of 15.4±5.6 mm Hg (Spearman's r=0.75, p<0.0001). Mean US-CCT was 544.56±40.0 µm compared with Corvis-CCT of 545.2±46.5 µm (Pearson's r=0.78, p<0.0001). Bland-Altman plots of all included eyes as well as subgroup analyses revealed good agreement of the IOP and CCT measurement techniques. High intraclass correlation coefficient values in 17 patients with repeated measurements revealed very good repeatability (0.942 and 0.937 for Corvis-IOP and Corvis-CCT, respectively). Corvis-IOP but not GAT showed a trend of dependence on CCT. Conclusions: Obtaining CCT and measuring IOP with the Corvis ST reveals very good repeatability and good accuracy in healthy subjects and patients with OHT and glaucoma when compared with standardised US pachymetry or GAT.